Nutritional status and health profile among single mothers in Malaysia - Sakinah, Harith; Noor Aini, Mohd Yusoff; Shariza, Abdul Razak; C.M, Teoh (2017)
According to the Population and Housing Census, Department of Statistics Malaysia, there are 126,810 single mothers among the 11.4 million women in Malaysia with Selangor has the highest number of single mothers (16,748) in the country(1) . Meanwhile, the amount of single mothers in Kelantan has been increased to 70,000 people, comprising both divorcees and widows. There are a total number of 16,344 single mothers whose aged less than 59 years old and 25,110 single mothers with the age range of more than 60 years old that are registered under Kelantan Secretariat of Women, Family and Welfare in 2014. The objective of this cross-sectional study is to determine the nutritional status and health profile of single mothers in Kota Bharu, Kelantan. A total of 100 single mothers aged 18-59 years old were involved in this study. Assessment of blood glucose, blood pressure, height and weight were done to each respondent. Food consumption based on the 24-hours diet recall was recorded and analyzed using Nutritionist Pro™ version 5.4.0 software. Results showed that the random blood glucose level of 82.0% single mothers was normal (within 4.4-8.0mmol/L), 18.0% exceeded 8.0mmol/L although only 10.0% of them were diagnosed with diabetes based on clinical history. Meanwhile, 46.0% had normal blood pressure level, 21.0% were under pre hypertension stage, 17.0% under stage 1 hypertension and 11.0% under stage 2 hypertension. However, based on their clinical history, only 24.0% were diagnosed with hypertension. It was found that the mean weight of single mothers was 62.00 ± 12.61 kg, the mean height was 150.97 ± 20.25 cm while Body Mass Index (BMI) was 26.20 ± 4.99 kg/m2 . The result showed that 33.0% of the subjects have normal BMI, 6.0% of them fall in the category of underweight, 39.0% were overweight and 22.0% were obese. Five percent of the subjects aged 19-29 years had meet 74.0% of the Recommended Nutrient Intake (RNI) of energy consumption for Malaysia, 57.0% aged 30-50 years achieved 70.6% of the RNI while 38.0% aged 50-59 years meet 69.5% of the RNI.This study indicate a high prevalence of overweight and obesity among single mothers and thus, it is suggested that future intervention programs should focus on preventing overweight and obesity problems related to chronic diseases.